In Situ Dispersive EXAFS in Electrocatalysis: The Investigation of the Local Structure of IrOx in Chronoamperometric Conditions as a Case Study. (31st December 2014) - Achilli, Elisabetta; Minguzzi, Alessandro; Lugaresi, Ottavio; Locatelli, Cristina; Rondinini, Sandra; Spinolo, Giorgio; Ghigna, Paolo
Abstract : An in situ study with dispersive EXAFS (Extended X-Ray Absorption Spectroscopy) at the Ir-L III edge is performed to characterize Electrodeposited Iridium Oxide Films (EIROF) under chronoamperometric conditions. The technique monitors the local chemical environment and electronic structure of iridium during the oxidation of Ir(III) to Ir(IV) with a time resolution of milliseconds. The study is performed in both acidic and basic media. The Fourier transforms of the time-resolved EXAFS signals clearly show that the short-range structure of Ir is similar to that of rutile-type IrO2 and is maintained during the reaction, thus accounting for the flexibility of the structure of the electrode material in accommodating different oxidation states. From a more general point of view, the work demonstrates the capabilities of in situ experiments based on state-of-the-art dispersive EXAFS in clarifying the mechanistic aspects of electrochemical processes.